2015
DOI: 10.2147/ijn.s84398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a micro/nano rough strontium-loaded surface on osseointegration

Abstract: We developed a hierarchical hybrid micro/nanorough strontium-loaded Ti (MNT-Sr) surface fabricated through hydrofluoric acid etching followed by magnetron sputtering and evaluated the effects of this surface on osseointegration. Samples with a smooth Ti (ST) surface, micro Ti (MT) surface treated with hydrofluoric acid etching, and strontium-loaded nano Ti (NT-Sr) surface treated with SrTiO 3 target deposited via magnetron sputtering technique were investigated in parallel for comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…39 36 female OVX rats HA-SLA electrochemical deposition 4, 8, 12 w Histomorphometry BIC BA Li et al . 35 40 female rats Smooth-Ti magnetron sputtering 12 w pull-out test Micro-CT Histomorphometry BIC BV/TV, Tb.N, Tb.Th, Tb.Sp, maximal push-out force Offermanns et al . 40 30 female rats Smooth-Ti magnetron sputtering process 4 w Histomorphometry BIC BA Andersen et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 36 female OVX rats HA-SLA electrochemical deposition 4, 8, 12 w Histomorphometry BIC BA Li et al . 35 40 female rats Smooth-Ti magnetron sputtering 12 w pull-out test Micro-CT Histomorphometry BIC BV/TV, Tb.N, Tb.Th, Tb.Sp, maximal push-out force Offermanns et al . 40 30 female rats Smooth-Ti magnetron sputtering process 4 w Histomorphometry BIC BA Andersen et al .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the surface topography changed by strontium incorporation process also contributed to bone-implant integration. Three of included studies revealed that micro/nanoscale topography enhanced new bone apposition and osseointegration of Sr-modified implants or had a synergistic effect with released Sr ions 28 , 29 , 35 . Hence, in-depth investigations are required to isolate the pure and independent effect of strontium or surface topography on improving bone-implant integration.…”
Section: Discussionmentioning
confidence: 99%
“…The cell behavior on AH-Ti may be ascribed to two reasons including the release of Na ions which can compromise the cell condition, 38 and the microstructure which has been proved to decrease the cell spread area. 37 The same inferior cell behavior on AH-Ti/ Sr150 was attributed to the excess amount of Sr, while the Sr amount on AH-Ti/Sr30 and AH-Ti/Sr90 was within the noncytotoxic level. 39 In addition, the AH-Ti/Sr groups (AH-Ti/Sr30, AH-Ti/Sr90, AH-Ti/Sr150) exhibited more stress fibers and actin microfilaments than control groups (AH-Ti, Ti), indicating the function of nanolayer formed by magnetron sputtering endowed the surface with numerous nanoscale cell attachment sites.…”
Section: Dovepressmentioning
confidence: 89%
“…The OD increased after the deposition of SrTiO 3 , indicating a better cell viability which was attributed to the release of strontium and the alternation of surface structure. 37 Whatis more, the AH-Ti/Sr90 group showed the highest optical density, while it was decreased in the AH-Ti/Sr150 group. Both the cell proliferation in four and seven days showed the same trend.…”
mentioning
confidence: 93%
See 1 more Smart Citation